Reduced mass transport resistance in polymer electrolyte membrane fuel cell by polyethylene glycol addition to catalyst ink. (1st January 2019) - Lee, Hye-Yeong; Kim, Sang-Kyung; Lee, Myeong-Rye; Peck, Dong-Hyun; Kang, Yun Chan; Kim, Chang-Soo
Abstract: Effects of Polyethylene glycol (PEG) addition to cathode catalyst ink were investigated by changing the addition amount of PEG. Performance of the polymer electrolyte membrane fuel cells (PEMFCs) increased and then decreased at the higher current density than 1.5 A/cm 2 as the amount of PEG addition increased. However, durability was not changed by the addition of PEG to the catalyst ink. Three different molecular weights of PEG were compared for PEG additives to cathode catalyst ink. Performance at high current density region increased and then decreased as PEG molecular weight increases from 200 to 10000. Increased performance by addition of PEG was attributed from reduced mass transport resistance. However, addition of large molecular weight PEG to catalyst ink reduced the performance because it lowered ionomer conductivity in the catalyst layer and then reduced proton transport resistance. Increased pore size in the catalyst layer and increased hydrophilicity on the electrode were also analyzed by addition of PEG to catalyst ink. Highlights: Performance of PEMFC increased at high current region by adding PEG to the catalyst ink. Mass transport resistance in the cathode decreased by adding PEG to catalyst ink. Enlarged pore size in the catalyst layer enhanced mass transfer.